Community Efforts in Fire Disaster Mitigation in Jelutung District, Jambi Province - Melda Yenni; Sugiarto Sugiarto; Reka Maiza Epralia (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
One of the efforts to prevent or minimize the potential impact of fire disasters in the future is mitigation and preparedness for fire disasters. Fire incidents in Jambi City in 2019 occu      rred in Jelutung District as many as 14 cases. The purpose of the study was to determine the role of the community in mitigating fire disasters. This research design is cross sectional. The research was conducted in Jelutung District. The research sample is the community in Jelutung District as many as 94 people taken by purposive sampling technique. Data collection techniques by interview using a questionnaire. Data were analyzed using chi square test. As many as 35.1% of respondents have poor fire disaster mitigation efforts, 43.9% of respondents have poor knowledge, 40.4% of respondents have poor attitudes, 42.6% of respondents have poor disaster warning systems. Bivariate results show that there is a relationship between knowledge (p-value = 0.000), attitudes (p-value = 0.000), disaster warning systems (p-value = 0.000) and fire disaster mitigation efforts. Fire disaster mitigation efforts in Jelutung Regency are related to knowledge, attitudes, and warning systems. It is hoped that the Jambi City Fire Service will always provide education about fire disaster mitigation.